PHONETICALLY MODIFIED PROPER NAMES IN MODERN JAPANESE: STATUS AND WAYS OF FORMING - Забуранна, О. (Київський національний університет імені Тараса Шевченка, 2023)
Background. This article draws attention to personal nominations in modern Japanese, the status of which is not clear, namely of nominations consisting of changed forms of names, surnames or their parts and often attached by various affixes (mainly by suffixes of respect). We propose to call such personal nominations phonetically modified anthroponyms. Methods. Using the linguistic methods of description and comparison, the article analyses phonetically modified anthroponyms in the first season of the popular television teen drama "Gokusen" (ごくせん), in the works of Japanese researchers on onomastics and comes up to conclusions below. Results. Phonetically modified anthroponyms are regarded to be a subset of names of endearments (愛称), street names (あだ名) or nicknames (ニックネーム). In another words they are a part of what can be called emotive personal nominations. In different types of those nominations their ratio varies. For example, they make up the majority of nicknames and approximately a quarter of street names. The main ways of forming such personal nominations are 1) the cutting of the surname and/or given name which often involves the emerging of special morae (/N/, /:/ /-/) and 2) various phonetic manipulations such as adding, eliminating or changing the order of the syllables or morae. To cut off, reduced or full elements of the proper name, syllables with sound-symbolic meaning as well as relatively semantically independent suffixes can be additionally attached. Although these ways are common for all kinds of emotive nominations, cut off names with added suffixes of respect ちゃん, さん, くん occur commonly among nicknames, and among street names – proper names with added or rearranged order of syllables (which more affects an imagery). The length of the original proper name, its phonetic and associative characteristics can limit the possibility of its phonetic modifications. Conclusions. Taking into consideration the fact that phonetically modified anthroponyms gain an emotivity, yet don't lose connections to the original anthroponyms, we maintain the view that they lay between original, neutral proper names and such street names which are based on the individual characteristics of person and have no relation to real name of their owner.

Вступ . Привернено увагу до особових номінацій сучасної японської мови, статус яких у японській лінгвістиці не є визначеним, а саме таких номінацій, які містять змінені форми імен, прізвищ чи їхні частини й часто доповнюються різними афіксами (найчастіше суфіксами поваги). Їх запропоновано називати фонетично модифікованими антропонімами. Методи . За допомогою методів лінгвістичного опису та порівняння у статті проаналізовано фонетично модифіковані антропоніми в популярному серіалі для молоді ごくせん ("Учителька-гангстер") і у працях із японської ономастики. Результати . Виявлено, що фонетично модифіковані антропоніми зазвичай вважають частиною пестливих імен (愛称), прізвиськ (あだ名) чи нікнеймів (ニックネーム). Водночас їхній питомий уміст у різних видах емотивних номінативів може відрізнятися, скажімо, вони складають переважну більшість нікнеймів і четвертину прізвиськ. До основних способів утворення таких номінацій належить усічення особового імені чи (/та) прізвища, яке часто супроводжується появою особливих мор японської мови (ん, っ, подовжених голосних), а також різні фонетичні маніпуляції, як-от додавання, віднімання чи перестановка складів (мор). До усічених, скорочених чи повних елементів власного імені можуть додаватися мори і склади зі звукосимволічним значенням чи й відносно семантично незалежні афікси. Хоча ці способи є спільними для всіх видів емотивних номінативів, але серед нікнеймів частіше виділяють усічення з додаванням суфіксів повагиちゃん, さん, くん, а серед прізвиськ – додавання чи перестановку складів, які сильніше впливають на образність. Довжина вихідного антропоніма, його фонетичні та асоціативні особливості можуть обмежувати можливості його фонетичної модифікації. Висновки . Оскільки такі номінації набувають емотивности й нової образности та не втрачають при цьому прямого зв'язку з вихідним антропонімом, дотримуємося думки про їхнє перехідне положення між стовідсотковими прізвиськами, які не пов'язані з іменем чи прізвищем і базуються на індивідуальних особливостях людини, і нейтральними нескороченими власними іменами.
ФОНЕТИЧНО МОДИФІКОВАНІ АНТРОПОНІМИ СУЧАСНОЇ ЯПОНСЬКОЇ МОВИ: СТАТУС І СПОСОБИ УТВОРЕННЯ
Keywords: emotive personal nominations; street names; names of endearments; nicknames; Japanese; onomastics; Japanese; емоційні номінативи; прізвиська; пестливі імена; нікнейми; японська мова; ономастика; сучасна японська мова